Digital Public Communication Innovation SHOLAWAT BRO: The Use of WhatsApp Broadcasting to Overcome Service Disinformation at UPT SAMSAT North Malang and Batu City - Aris Sunarya; Mariah bt Darus; Sri Khamariyah; Widyawati Widyawati; Nihayatus sholichah (JOURNAL OF ADMINISTRATIVE AND SOCIAL SCIENCE, 2024)
Disinformation in public services is a systemic problem that hampers bureaucratic efficiency and directly harms citizens, particularly in motor vehicle administration units with dynamic procedures and frequently changing regulations. This study aims to analyze the SHOLAWAT BRO (Sosialisasi Lewat Whatsapp Broadcasting) innovation as a WhatsApp Broadcasting-based digital public communication system developed by UPT SAMSAT Malang Utara and Batu Kota to address service disinformation. The analysis was conducted using two theoretical frameworks: Rogers' Diffusion of Innovation Theory (2003) through five innovation attributes and Cangara's Digital Public Communication Model (2016) through six communication elements. This study employed a descriptive qualitative approach with data collection techniques consisting of in-depth interviews with seven informants, non-participatory observation, and documentation study, analyzed using the interactive model of Miles, Huberman, and Saldaña (2014) with data validity established through source and method triangulation. The findings indicate that SHOLAWAT BRO fulfills all innovation diffusion attributes and public communication elements synergistically, resulting in a decrease in document rejection rates from 8.5 percent to 1.7 percent, an 88.35 percent reduction in disinformation complaints, an increase in the Community Satisfaction Index on the information aspect from 2.61 to 3.71 on a four-point scale, and a 734.8 percent growth in registered contacts over three years of implementation. This study concludes that SHOLAWAT BRO represents an effective, inclusive, and highly replicable anti-disinformation digital public communication model for other public service agencies in Indonesia within the framework of bureaucratic digital transformation.